Une famille et des professionnels médicaux face au cancer. Incertitudes et contraintes au Cambodge - Meriem M’Zoughi (Anthropologie & Santé)
This article describes the cancer experience of a child and her family in Cambodia. She is a four-year-old girl whose therapeutic wandering is characteristic of the weaknesses and flaws of the Cambodian health care system. The child was treated with chemotherapy for several months against MALT lymphoma (a non-Hodgkin’s lymphoma), before being diagnosed Burkitt lymphoma. This experience shows how health organization shapes certain logics of care in a country where the therapeutic sphere is coordinated by families. The aim here is to highlight the pragmatism and coping strategies of caregivers and medical professionals in a difficult social, economic, material and emotional context that is not conducive to longitudinal medical care.